Effects of Ozone on Egg Shell Microbial Load, Hatching Traits and Chick Performance in Quail Eggs - Koc, Sedat; Aygun, Ali (Innoriginal: International Journal of Sciences, 2021)
Objective: The aim of this study was to establish the effects of ozone on eggshell total aerobic mesophilic bacteria, egg weight loss, hatching traits, embryo deaths and chick performance. Methods: A total of 825 fresh hatching quail eggs were randomly distributed into five groups. Treatment groups were formed as control group (benzalkonium cloride application; C), 1% ozone application (O1), 3% ozone application (O3), 5% ozone application (O5) and 7% ozone application (O7). Results: There were no significant differences between the groups in terms of egg weight loss, hatching traits, embryo deaths, chick performance and livability. Ozone treatment had lower levels of total bacteria, especially in O7 group, than control eggs for the entire incubation period. Conclusion: As a result, the application of ozone can be used as an alternative to natural chemical disinfectant without adversely affecting the incubation results and chick performance.